2020
DOI: 10.1111/and.13861
|View full text |Cite
|
Sign up to set email alerts
|

Normal sperm parameters per se do not reliably account for fertility: A case–control study in the real‐life setting

Abstract: A proportion of men are infertile despite having normal medical history/physical examination and normal semen analysis. We aimed to assess whether normal sperm parameters per se account for male factor fertility. 1,957 infertile men were compared with 103 age-comparable fertile controls. Semen analysis was based on 2010 World Health Organization reference criteria. Of all, 12.1% of infertile men and 40.8% of fertile men presented with normal sperm parameters. Among fertile men, 36.9% had isolated sperm abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 32 publications
(35 reference statements)
0
31
0
Order By: Relevance
“…Hence, the tendency of only concentrating on female reproductive health has a major impact on the success rates of ART when it comes to evaluate both partners. 34 Taking together these observations, we have investigated the trends of infertile men presenting for their first andrological evaluation after previous ART (one or even more cycles), assessing potential differences with a cohort of patients belonging to infertile couples that, conversely, have been not submitted to (any) ART throughout the same time frame. Of major clinical importance, we found that approximately 15% of couples presented for a first andrological evaluation after previous failed attempts of ART (one or even more) during the entire 17-year time frame.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, the tendency of only concentrating on female reproductive health has a major impact on the success rates of ART when it comes to evaluate both partners. 34 Taking together these observations, we have investigated the trends of infertile men presenting for their first andrological evaluation after previous ART (one or even more cycles), assessing potential differences with a cohort of patients belonging to infertile couples that, conversely, have been not submitted to (any) ART throughout the same time frame. Of major clinical importance, we found that approximately 15% of couples presented for a first andrological evaluation after previous failed attempts of ART (one or even more) during the entire 17-year time frame.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, even men with normal semen parameters may not be able to achieve a successful physiological pregnancy due to underlying semen abnormalities (i.e., oxidative stress). 34 The evaluation of the male partner of every infertile couple is important for a number of reasons. First, even though a semen analysis has been considered historically the cornerstone to establishing the reproductive potential of the male, several studies have shown that a significant proportion of men are infertile despite having normal sperm analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Important limitations of those studies were the small samples size and the lack of information about the fertility status of the normozoospermic control groups. This significance of this study relies on: i) the large cohort of infertile men evaluated by a single expert uro/andrologist with a comprehensive diagnostic work-up; and, ii) the presence of a control group of fertile men with either normal and abnormal semen analyses [56], including iTZS, thus recapitulating the everyday clinical practice. Of utmost importance, this study is novel since it is the first to comprehensively compare infertile men according to isolated sperm abnormalities.…”
Section: Plos Onementioning
confidence: 99%